Insight to pyrazinamide resistance inMycobacterium tuberculosisby molecular docking - Unissa, Amirudeen Nusrath (Biomedical Informatics, 2009)
Pyrazinamide (PZA) - an important drug in the anti-tuberculosis therapy, activated by an enzyme Pyrazinamidase (PZase). The basis of PZA resistance in Mycobacterium tuberculosis was owing to mutation in pncA gene coding for PZase. Homology modeling of PZase was performed using software Discovery Studio (DS) 2.0 based on the crystal structure of the PZase from Pyrococcus horikoshii (PDB code 1im5), in this study. The model comprises of one sheet with six parallel strands and seven helices with the amino acids Asp8, Asp49, Trp68, Lys96, Ala134, Thr135 and Cys138 at the active site. Five mutants were generated with Gly at position 8, Thr at position 96, Arg at position 104, Tyr and Ser at position 138. The Wild-type (WT) and five mutant models were docked with PZA. The results indicate that the mutants Lys96Thr, Ser104Arg Asp8Gly and Cys138Tyr may contribute to higher level drug resistance than Cys138Ser. These models provide the first in-silico evidence for the binding interaction of PZA with PZase and form the basis for rationalization of PZA resistance in naturally occurring pncA mutant strains of M. tuberculosis.